Pengaruh Pembenah Tanah Cair dan Pupuk N, P, K terhadap Pertumbuhan Serta Hasil Tanaman Bawang Merah (Allium cepa, L.) - Solihin, Eso; Sudirja, Rija; Yuniarti, Anni; Kamaluddin, Nadia Nuraniya (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the effects of humic acid application on soil pH, organic carbon (C-Organic), cation exchange capacity (CEC), as well as the growth and yield of shallots. The study was conducted at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang, from November 2023 to February 2024. The experimental method used was a Randomized Complete Block Design (RCBD) with six treatments and five replications. The treatments were: A; (0.5 Soil Amendment and 1 Standard N, P, K), B; (1 Soil Amendment and 1 Standard N, P, K), C; (1.5 Soil Amendment and 1 Standard N, P, K), E; Without Standard N, P, K and Soil Amendment (Control), and F; (Standard N, P, K). The results showed that the combination of soil amendments and N, P, and K fertilizers significantly affected the parameters of soil pH, C-Organic, CEC, and plant height at 14, 28, 42, and 56 days after planting (DAP); stem diameter at 14, 28, 42, and 56 DAP; number of tillers at 14, 28, 42, and 56 DAP; and shallot plant weight.